1996
DOI: 10.1021/jp960993g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Analysis of Single and Mixed Micelle Systems of SDS and DTAB

Abstract: Structural features of the single and mixed micellar systems of sodium dodecyl sulfate (SDS) and dodecyltrimethylammonium bromide (DTAB) were characterized using the fluorescence probe 6-propionyl-2-(dimethylamino)naphthalene (Prodan). In particular, our investigations capitalized on the spectral sensitivity of Prodan to its environment as well as the extensive solubility of Prodan in solvents of varying polarity and/or hydrophobicity to effectively use a three-mode factor analysis technique to resolve the coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 22 publications
(40 reference statements)
4
59
0
Order By: Relevance
“…Karukstis et al 45 proposed the use of PRODAN as a novel and powerful probe to study the presence of different microenvironments in aqueous and nonaqueous solutions. The structure of PRODAN is presented in Fig.…”
Section: Prodan and Its Environmental Sensitivitymentioning
confidence: 99%
“…Karukstis et al 45 proposed the use of PRODAN as a novel and powerful probe to study the presence of different microenvironments in aqueous and nonaqueous solutions. The structure of PRODAN is presented in Fig.…”
Section: Prodan and Its Environmental Sensitivitymentioning
confidence: 99%
“…These changes can include variations in both the size and shape of the micelle, as well as variations in their chemical properties. Fluorescence investigations using a variety of probes have shown that the interiors of surfactant micelles display increased hydrophobic character in the presence of salt concentrations as low as 5 mM [17][18][19]. Previous work in our laboratory has indicated that the addition of small amounts of NaCl to BGEs containing SDS can have a significant impact on the separation of complex mixtures [20].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of mixed micelles for aqueous mixtures of C12TAB and SDS is discussed in various reports [31][32][33][34][35][36][37]. A strong electrostatic interaction between anionic SDS and cationic DTAB leads to formation of spherical mixed micelles at dilute conditions and equal molar ratios, which transform to stable large vesicles at specific molar ratio of surfactant components [37].…”
Section: Influence Of Dodecyl Trimethylammonium Bromide (Dtab) On Conmentioning
confidence: 99%